Storminess over the North Atlantic and northwestern Europe—A review. (19th May 2014) - Feser, F.; Barcikowska, M.; Krueger, O.; Schenk, F.; Weisse, R.; Xia, L.
Abstract This review assesses storm studies over the North Atlantic and northwestern Europe regarding the occurrence of potential long‐term trends. Based on a systematic review of available articles, trends are classified according to different geographical regions, datasets, and time periods. Articles that used measurement and proxy data, reanalyses, regional and global climate model data on past and future trends are evaluated for changes in storm climate. The most important result is that trends in storm activity depend critically on the time period analysed. An increase in storm numbers is evident for the reanalyses period for the most recent decades, whereas most long‐term studies show merely decadal variability for the last 100–150 years. Storm trends derived from reanalyses data and climate model data for the past are mostly limited to the last four to six decades. The majority of these studies find increasing storm activity north of about 55–60° N over the North Atlantic with a negative tendency southward. This increase from about the 1970s until the mid‐1990s is also mirrored by long‐term proxies and the North Atlantic Oscillation and constitutes a part of their decadal variability. Studies based on proxy and measurement data or model studies over the North Atlantic for the past which cover more than 100 years show large decadal variations and either no trend or a decrease in storm numbers. Future scenarios until about the year 2100 indicate mostly an increase in winter storm intensity over the North Atlantic and western Europe. However, future trends in total storm numbers are quite heterogeneous and depend on the model generation used.